Impact of Board Composition of Philippine Companies on the Quality of their ESG Disclosures - Nery, Justin Reginald F; Morales, Marc Kevin L (Philippine Management Review, 2023)
Do independence and diversity in the board result in better quality of ESG disclosures? This research answers this question by exploring whether certain aspects of the board composition of listed firms in the Philippines positively affect the quality of ESG disclosures. The authors have found that board gender diversity has a significant positive effect on the quality of ESG disclosures, while they cannot definitively conclude on the impact of board independence, CEO duality, and board size. Nevertheless, firms that seek to improve independence in the board should do so not only for improving ESG disclosure score but also primarily for improving representation of stakeholders and minority shareholders, which is consistent with good corporate governance. The findings of this research further support the importance of independence and diversity in corporate governance.